Zakat on Non-Cash Employment Benefits: A Maqasid al-Shariah Framework - Zahri, Fatin ‘Alia; Zahri, Mohd. ‘Adli; Ambak, Azlinah; Husen Ismail, Faisal; Hamat, Zahri (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2025)
This study explores the zakatability of Benefits in Kind (BIK)—non-cash employment benefits such as housing, transport, and utilities—within the framework of Maqasid al-Shariah. Although these benefits are subject to taxation under Malaysia’s Inland Revenue Board (IRB) guidelines, they are typically excluded from zakat assessments by State Islamic Religious Councils (SIRCs). This gap raises concerns regarding distributive justice and the spiritual objective of wealth purification. Drawing on classical and contemporary Islamic jurisprudence, particularly the principles of qiyas, maslahah, and istihsan, this paper argues that BIK constitutes wealth (mal) and should be included in zakat assessments. The study employs qualitative content analysis of fatwa literature, AAOIFI zakat accounting standards, and BIK valuation models applied by the IRB. Findings suggest that excluding BIK contradicts zakat's ethical and redistributive purposes, especially in urban contexts where BIK significantly enhances financial capacity. The paper recommends adopting standardized valuation practices from the IRB, issuing a national-level fatwa, implementing Shariah-compliant audit mechanisms, and public awareness campaigns to improve compliance and governance. These reforms ensure justice and equity and align Malaysia’s zakat practices with the dynamic realities of modern compensation structures. The paper concludes with policy recommendations for harmonizing zakat and taxation systems, thereby strengthening the institutional credibility, transparency, and effectiveness of zakat as a tool for socioeconomic justice.